BEBAS CEMAS SELAMA HAMIL - Selvia Nurul Qomari; Nailufar Firdaus (STIKES NGUDIA HUSADA MADURA, 2020)
For primigravida mothers, anxiety will be even more pronounced when the mother enters the third trimester of pregnancy. This is because primigravida pregnant women will face a labor process that she has never experienced before. It is not impossible that prolonged anxiety in pregnant women will have a negative impact on both the mother and the fetus. Aprilia & Richmond (2011). This activity aims to increase knowledge of pregnant women and their families, reduce anxiety in pregnant women and increase knowledge about midwifery science updates.The community service method is by collecting data on pregnant women at the local Bangkalan midwife, after that collecting all pregnant women on the specified day and explaining the objectives of community service and conducting counseling about anxiety to pregnant women, with two counseling materials, yaotu endorphin massage and continued with the material Progressive Auto Relaxation (ROP). After that, a demonstration of how to do endorphin massage and Progressive Oto Relaxation (ROP) was demonstrated.The event went smoothly and was attended by 24 pregnant women who were accompanied by their families. The material presented was anxiety-free during pregnancy using leaflets. Overall, the participants understood how to reduce anxiety in pregnant women. One pregnant woman who volunteered to demonstrate endorphine massage was able to do it well.This community service activity is based on research by Selvia (2019) showing that therapy with ROP and Endorphine massage can be done to reduce anxiety in pregnant women.